Effects of Avitinib on CYP450 Enzyme Activity in vitro and in vivo in Rats - Shi Y; Meng D; Wang S; Geng P; Xu T; Zhou Q; Zhou Y; Li W; Chen X (Dove Medical Press, 2021)
Yong Shi,1,* Deru Meng,1,* Shuanghu Wang,1 Peiwu Geng,1 Tao Xu,2 Quan Zhou,1 Yunfang Zhou,1 Wanshu Li,3 Xugao Chen4 1Comprehensive Breast Health Center, Department of Thyroid and Breast Surgery, The Sixth Affiliated Hospital of Wenzhou Medical University, The People's Hospital of Lishui, Lishui, 323000, People's Republic of China; 2Department of Pharmacy, Ningbo First Hospital, Ningbo, 315010, Zhejiang, People's Republic of China; 3Department of Pharmacy, Ningbo Municipal Hospital of Traditional Chinese Medicine, Ningbo, 315010, Zhejiang, People's Republic of China; 4Department of Radiology, The Sixth Affiliated Hospital of Wenzhou Medical University, The People's Hospital of Lishui, Lishui, 323000, People's Republic of China*These authors contributed equally to this workCorrespondence: Xugao ChenDepartment of Radiology, The Sixth Affiliated Hospital of Wenzhou Medical University, The People's Hospital of Lishui, Lishui, 323000, People's Republic of ChinaTel/Fax +86578-2780081Email lishui001@163.comWanshu LiDepartment of Pharmacy, Ningbo Municipal Hospital of Traditional Chinese Medicine, Ningbo, 315010, Zhejiang, People's Republic of ChinaTel/Fax +86574-87089100Email wanshu_lws@126.comPurpose: Avitinib is the first third-generation epithelial growth factor receptor (EGFR) inhibitor independently developed in China and is mainly used for treating non-small cell lung cancer. However, pharmacokinetic details are limited. This study explored the in vivo and in vitro effects of avitinib on cytochrome CYP450 enzymes metabolic activity.Methods: A rapid and sensitive ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method was developed and validated for determining six probe substrates and their metabolites. Avitinib influence on activity levels of CYP isozymes was examined in vitro using human and rat liver microsomes (HLMs/RLMs). For in vivo studies, rats were pretreated with 30 mg/kg avitinib once daily for 7 days (avitinib multiple-doses group), 30 mg/kg avitinib on day 7 (avitinib single-dose group), or an equivalent amount of CMC-Na once daily for 7 days (control group), followed by intragastrical administration of the probe substrates (1 mg/kg tolbutamide and 10 mg/kg phenacetin, bupropion, chlorzoxazone, dextromethorphan, and midazolam). Plasma pharmacokinetics and IC50 values of the probe substrates were then compared. Pharmacokinetic parameters were determined using non-compartmental analysis implemented in a pharmacokinetic program.Results: In vitro experiments revealed different inhibitory effects of avitinib on the six probe substrates with various IC50 values (bupropion, 6.39/22.64 μM; phenacetin, 15.79/48.36 μM; chlorzoxazone, 23.15/57.09 μM; midazolam, 27.64/59.6 μM; tolbutamide, 42.18/6.91 μM; dextromethorphan, 44.39/56.57 μM, in RLMs and HLMs respectively). In vivo analysis revealed significant differences (P < 0.05) in distinct pharmacokinetic parameters (AUC(0-t), AUC (0-∞), Cmax, MRT(0-t), MRT (0-∞), and CLz/F) for the six probe substrates after avitinib pretreatment.Conclusion: A sensitive and reliable UPLC-MS/MS method was established to determine the concentration of six probe substrates in rat plasma. Avitinib had inhibitory effects on CYP450 enzymes, especially cyp2b1, cyp1a2 in RLMs, CYP2C9 in HLMs, and cyp1a2, cyp2b1, cyp2d1, and cyp2e1 in vivo. Our data recommend caution when avitinib was taken simultaneously with drugs metabolized by CYP450 enzymes.Keywords: cytochrome, EGFR inhibitor, UPLC-MS/MS, rat liver microsome, drug-drug interaction